Analysis of Implementation of Perioperative Care Instrument Based on Standards of Nursing Diagnosis, Intervention and Outcomes in Indonesia - Haris Widodo; Nursalam Nursalam; Erna Dwi Wahyuni (Universitas Airlangga, 2020)
Introduction: Perioperative nursing care has been widely applied in either various hospitals or other healthcare facilities. The purpose of this study was to analyze the implementation of a perioperative care instrument based on the Indonesian Nursing Diagnosis Standards (SDKI, the Indonesian Nursing Intervention Standards (SIKI), and the Indonesian Nursing Outcome Standards (SLKI) in the operating room in a Teaching hospital, East Java.Methods: This research design was a descriptive study. The study population was the perioperative nursing care instrument in the medical records of patients with fracture cases. The research sample consisted of 106 medical records with total sampling. The dependent variable of this study was the implementation of the perioperative nursing care instrument based on SDKI, SLKI, and SIKI. Data were collected using observation sheets and analyzed using descriptive analysis.Results: Applying the diagnosis of nursing care according to the standard the risk of infection is (27.36%), acute pain (20.75%), and the risk of injury (2.83%). The application of nursing outcomes according to standards is the infection rate (27.36%), pain level (20.75%) and fluid balance (2.83%).Conclusion: The nursing interventions, implementation, and evaluation of nursing are not according to the Indonesian Nursing Intervention standards (SIKI). The application of perioperative nursing care instruments, which includes titles, diagnoses, and outcomes, is partly following SDKI and SLKI standards. Nursing interventions, implementation, and evaluation of nursing are not according to standards.